Glass fiber based molecular sieve / aluminum fumaric acid MOF composite adsorbent as well as synthesis method and application thereof

By synthesizing molecular sieve and aluminum fumaric acid MOF in situ on glass fiber paper to form a composite adsorbent, the problems of low adsorption amount and high desorption temperature of existing adsorbents under low humidity are solved, and high efficiency and low energy consumption are achieved.

CN120132805APending Publication Date: 2025-06-13JIANGSU JOSEM ENVIRONMENTAL EQUIP MFG CO LTD

Patent Information

Application Number
CN202510154179.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-06-13

AI Technical Summary

Technical Problem

The existing adsorbents used for deep dehumidification have low adsorption amount and high desorption temperature at low humidity, resulting in high energy consumption and difficult to adapt to the needs of different humidity environments.

Method used

The molecular sieve and aluminum fumaric acid MOF composite adsorbent were used to uniformly load the molecular sieve and aluminum fumaric acid MOF on glass fiber paper through in-situ synthesis method, and the water vapor adsorption isothermal curve is adjusted to adapt to different humidity environments.

Benefits of technology

It achieves the effects of high water adsorption capacity, high balanced adsorption capacity and low desorption temperature under low humidity. It is suitable for different dehumidification environments, and has high load and strong binding force, avoiding the problem of easy falling off of powder adsorbent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120132805A_ABST
    Figure CN120132805A_ABST
Patent Text Reader

Abstract

The invention discloses a glass fiber based molecular sieve / aluminum fumaric acid MOF composite adsorbent as well as a synthesis method and application thereof, and belongs to the technical field of adsorbents for rotary dehumidifiers. The synthesis method comprises the following steps: preparing a molecular sieve, sodium fumarate, a film-forming agent, a polymer thickening agent and deionized water into uniform dispersion liquid; immersing glass fiber paper into the dispersion liquid, and drying to obtain glass fiber paper containing molecular sieve / sodium fumarate; the preparation method comprises the following steps: preparing a mixed solution from an aluminum salt, ethanol and deionized water, immersing glass fiber paper containing molecular sieve / sodium fumarate into the mixed solution, carrying out an in-situ crystallization reaction, washing with water, and drying to obtain the glass fiber based molecular sieve / aluminum fumaric acid MOF composite adsorbent. According to the synthesis method, the traditional molecular sieve and the aluminum fumaric acid MOF are compounded to form the composite adsorbent, the requirements of low-temperature desorption and high adsorption capacity can be met at the same time, and modulation of the adsorption isotherm between the molecular sieve and the aluminum fumaric acid MOF can be achieved by adjusting the ratio of the molecular sieve to the aluminum fumaric acid MOF.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of adsorbents for rotary dehumidifiers, and particularly relates to a glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent, a synthesis method thereof, and an application thereof. Background Art

[0002] With the rapid development of industry and the continuous improvement of people's living standards, the requirements for humidity in the living environment and industrial fields are increasing day by day, especially in the field of lithium-ion batteries that require deep dehumidification. At present, the core component of the humidity control system for deep dehumidification is a dehumidification rotor using traditional silica gel and aluminosilicate molecular sieve as adsorbents. Silica gel has a low cost and a large adsorption capacity at high humidity; due to its regular microporous structure and high specific surface area, molecular sieve exhibits excellent adsorption performance at low humidity; however, silica gel has a low adsorption capacity at low humidity, and the molecular sieve has a high desorption temperature (250 °C). The use of a double-rotor process (front silica gel wheel, rear molecular sieve wheel) or a silica gel / molecular sieve composite adsorbent dehumidification rotor process can achieve deep dehumidification, but its energy consumption is still relatively high. Therefore, aiming at adsorbents with low cost, low desorption temperature, and high moisture absorption performance, the development of a low-temperature desorption dehumidification rotor has theoretical guiding significance and practical application value.

[0003] The emergence of new metal-organic framework materials (MOFs) provides an opportunity for the research and development of low-temperature desorption dehumidification rotors. Among numerous MOF materials, aluminum fumarate MOF (trade name A520) is a reasonable choice for low-temperature desorption rotors due to its low raw material price, low synthesis energy consumption, rapid reaction, and characteristics such as S-shaped adsorption isotherm, high moisture absorption capacity, and low desorption temperature. For example, Chinese invention patent with publication number CN110523380A discloses a honeycomb ceramic-based aluminum-fumarate MOF adsorbent and its in-situ synthesis method. Fumaric acid, an alkaline substance, and water are mixed evenly, a thickening agent is added and mixed evenly to obtain a mixed solution. The honeycomb ceramic matrix is impregnated in the mixed solution and dried to obtain a matrix containing deprotonated fumaric acid. The matrix containing deprotonated fumaric acid is impregnated in an aluminum salt solution, heated in a water bath, cooled to room temperature, the precipitate is filtered, washed, dried, and sintered and activated by heating to obtain the honeycomb ceramic-based aluminum-fumarate MOF adsorbent. The obtained adsorbed active substance is evenly and densely distributed on the honeycomb ceramic fiber matrix with a high loading amount. The adsorbent has a low crystallization temperature and a fast rate; the product shows an S-shaped water vapor adsorption isotherm, with a fast adsorption rate, a high equilibrium adsorption amount, and easy desorption, and can be applied to the preparation of adsorption dehumidification rotors or total heat recovery devices. Nevertheless, the steeply rising region of the S-type of this kind of aluminum-fumarate MOF is at 20-40%RH. When the humidity is below 25%RH, its moisture absorption amount is quite small; while the traditional molecular sieve has a type I adsorption curve, and even when the humidity is 10%RH, its adsorption amount is still relatively high. However, its desorption temperature is high, the regeneration energy consumption is large, and when the humidity is above 40%RH, its moisture absorption amount is relatively low. How to obtain an adsorbent with characteristics such as an adjustable water adsorption isotherm curve, high water adsorption capacity at low humidity, high equilibrium adsorption amount, and low desorption temperature has become an urgent problem to be solved at present. Summary of the Invention

[0004] The technical problem to be solved by the present invention is: how to synthesize an adsorbent with characteristics such as an adjustable water adsorption isotherm curve, high water adsorption capacity at low humidity, high equilibrium adsorption amount, and low desorption temperature, and which can be applied to the rotor dehumidification industry for low-temperature desorption in different environments.

[0005] To solve the above technical problem, the technical solution adopted by the present invention is: a synthesis method of a glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent, comprising the following steps: S1. Under stirring conditions, molecular sieve, sodium fumarate, film-forming agent, and thickening agent are taken and added to deionized water to prepare a uniformly dispersed solution to obtain a molecular sieve / sodium fumarate dispersion; Under stirring conditions, an aluminum salt is taken and added to a mixed solution composed of ethanol and deionized water. After the aluminum salt is completely dissolved and evenly dispersed, a mixed solution is obtained; S2. Immerse the glass fiber paper in the molecular sieve / sodium fumarate dispersion until it is completely wetted, then take it out and dry it to obtain the glass fiber paper containing molecular sieve / sodium fumarate; S3. Immerse the glass fiber paper containing molecular sieve / sodium fumarate in the mixed solution for crystallization reaction. After the crystallization reaction, wash and dry it in sequence to obtain the glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent.

[0006] The beneficial effects of the present invention are as follows: The synthesis method provided by the present invention uses the glass fiber paper as the substrate. Under the stirring and with the assistance of the water-soluble film-forming agent and the hydrophilic polymer thickener, the glass fiber paper is impregnated in the molecular sieve / sodium fumarate dispersion. Due to the strong bonding property between the molecular sieve / sodium fumarate dispersion and the glass fiber paper, the molecular sieve / sodium fumarate can be evenly loaded on the glass fiber paper. At the same time, sodium fumarate can complex with the aluminum salt to undergo a crystallization reaction, and the molecular sieve does not react with the aluminum salt solution. When the glass fiber paper loaded with molecular sieve / sodium fumarate is immersed in the aluminum salt mixed solution, the sodium ions in sodium fumarate and the aluminum ions in the aluminum salt solution will undergo ion exchange. Under a certain crystallization temperature and reaction time, a glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent is formed. The synthesis method provided by the present invention has the characteristics of environmental friendliness, and can obtain an adsorbent with a high equilibrium adsorption capacity, a low desorption temperature, not easy to fall off, and a high water vapor adsorption capacity. Description of the Drawings

[0007] Figure 1 The water vapor isothermal adsorption curves of the samples of the examples and comparative examples of the specific embodiments of the present invention are shown; Figure 2 The X-ray diffraction spectra of the samples of the examples and comparative examples of the specific embodiments of the present invention are shown. Specific Embodiments

[0008] To describe the technical content, the achieved purpose and the effects of the present invention in detail, the following is described in combination with the embodiments and with reference to the drawings.

[0009] A synthesis method of a glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent includes the following steps: S1. Under stirring conditions, take molecular sieve, sodium fumarate, film-forming agent and thickener and add them into deionized water to prepare a uniform dispersion to obtain the molecular sieve / sodium fumarate dispersion; Under stirring conditions, take aluminum salt and add it into the mixed solution composed of ethanol and deionized water. After the aluminum salt is completely dissolved and evenly dispersed, a mixed solution is obtained; S2. Immerse the glass fiber paper in the molecular sieve / sodium fumarate dispersion until the paper is completely wetted, then take it out and dry it to obtain the glass fiber paper containing molecular sieve / sodium fumarate; S3. Immerse the glass fiber paper containing molecular sieve / sodium fumarate in the mixed solution for crystallization reaction, take it out, wash and dry it successively to obtain the glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent.

[0010] As can be seen from the above description, the beneficial effects of the present invention are as follows: The glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent provided by the present invention adopts an in-situ synthesis method, using a glass fiber paper as the substrate. The glass fiber paper is impregnated in a dispersion containing molecular sieve / sodium fumarate. Under the action of a water-soluble film-forming agent and a hydrophilic polymer thickener, a glass fiber paper containing molecular sieve / sodium fumarate is formed. Then, the paper is placed in an aluminum salt mixed reaction solution for crystallization, washed and dried to prepare the glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent. The synthesis method provided by the present invention can regulate the water vapor adsorption isotherm curve by adjusting the ratio of molecular sieve / aluminum fumarate MOF, so that it can be adjusted between the adsorption curves of molecular sieve and aluminum fumarate MOF, and can be applied to different dehumidification environments. The prepared composite adsorbent (dehumidification rotor core) can be applied to the adsorption type low-temperature desorption dehumidification rotor for deep dehumidification.

[0011] By adding a film-forming agent, the hydrophilic property of the glass fiber substrate can be increased, and at the same time, a hydrophilic film is formed on the substrate, so that the amount of sizing of the synthesized molecular sieve / aluminum fumarate MOF is large and it is not easy to fall off from the substrate, that is, the phenomenon of powder falling is not easy to occur. By adding a thickener, the sizing amount of the glass fiber paper for molecular sieve and sodium fumarate can be increased, so as to synthesize more target products. Ethanol and deionized water form a green mixed solvent. The addition of ethanol can be used as an antisolvent to reduce the solubility of aluminum salt in water, facilitate the migration of aluminum ions to the glass fiber substrate and complex with fumarate ions to form aluminum fumarate MOF. Usually, the carrier of powder materials is a porous substrate, including inorganic porous substrates and organic porous substrates; inorganic substrates such as porous ceramics, porous glass, sepiolite, cordierite, etc.; organic porous substrates such as polyurethane sponge, melamine sponge, etc. The glass fiber paper has low basis weight (20~25g / m 2 ), high voids, good mechanical properties, and characteristics such as corrosion resistance and high temperature resistance. Combining it with molecular sieve and aluminum fumarate MOF as the substrate (in-situ synthesis) to form a glass fiber-based molecular sieve and aluminum fumarate MOF composite adsorbent, and further developing a low-temperature desorption dehumidification rotor has broad application prospects.

[0012] In one or more embodiments, the temperature of the crystallization reaction in S3 is 30~80°C, and the time is 2~10h. Preferably, the crystallization temperature is 40~70°C, and the time is 4~8h. If the crystallization temperature is too low, the reaction rate is slow and the sizing amount of aluminum fumarate on the glass fiber is small; if the temperature is too high, the reaction rate is fast, resulting in the shedding of aluminum fumarate. If the crystallization time is too short, the sizing amount of aluminum fumarate on the glass fiber will be small; if the time is too long, the aluminum fumarate will fall off.

[0013] In one or more embodiments, the mass ratio of the molecular sieve to the sodium fumarate in S1 is 2:8 to 8:2, preferably 3:7 to 7:3. If the amount of the molecular sieve is too small, the content of the molecular sieve in the synthesized molecular sieve / aluminum fumarate MOF composite adsorbent is small, which will lead to a small change in the adsorption / desorption isotherm curve of the aluminum fumarate MOF; on the contrary, if the amount of the molecular sieve is too large, the desorption temperature of the product will be high.

[0014] In one or more embodiments, the molecular sieve is one of 3A, 4A, 5A, and 13X. Considering factors such as the moisture absorption amount, desorption temperature, and application range of the material, the molecular sieve is preferably 13X molecular sieve.

[0015] In one or more embodiments, the addition amount (by mass) of the film-forming agent in S1 is 0.5 to 2% of the molecular sieve / sodium fumarate dispersion, preferably 0.8 to 1.8%.

[0016] The film-forming agent is one of chitosan hydrochloride, carboxymethyl chitosan, and sodium carboxymethyl cellulose (CMC). Considering factors such as the film-forming effect on the substrate, hydrophilic property, and price of the film-forming agent, the water-soluble film-forming agent is preferably chitosan hydrochloride.

[0017] In one or more embodiments, in S1, the addition amount (by mass) of the thickening agent is 0.5 to 1.5% of the molecular sieve / sodium fumarate dispersion, preferably 0.8 to 1.3%. If the amount of the thickening agent added is too small, the molecular sieve and sodium fumarate are not easily attached to the glass fiber embryo; if the amount of the thickening agent added is too large, the viscosity of the dispersion is too high, resulting in uneven distribution of the molecular sieve and sodium fumarate attached to the embryo.

[0018] In one or more embodiments, the thickening agent is one of polyethylene glycol (PEG), polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), and guar gum (GG). Considering the addition amount of the thickening agent and the thickening effect, guar gum is preferred.

[0019] In one or more embodiments, in S1, the mass fraction of the aluminum salt in the mixed solution is 5 to 25%, preferably 8 to 20%. If the amount of the aluminum salt added is too low, the migration rate of the aluminum salt to the embryo is slow, and the aluminum salt cannot fully crystallize with the sodium fumarate; if the amount of the aluminum salt added is too high, the crystallization rate is fast, the crystallinity of the reaction product is reduced, and the crystals are unevenly dispersed on the embryo.

[0020] In one or more embodiments, the aluminum salt is one of aluminum chloride, aluminum sulfate, aluminum nitrate, and alum. Considering the solubility of the aluminum salt and the loading amount on the substrate, aluminum sulfate is preferred.

[0021] In one or more embodiments, when preparing the mixed solution in S1, the mass ratio of ethanol to deionized water is 0.1~0.5:1. Preferably, it is 0.15~0.4:1. If the amount of ethanol added is too small, the anti-solvent effect is small, the amount of glue on the substrate of the obtained composite adsorbent is low, and the product is prone to powder loss; if the amount of ethanol added is too much, the aluminum salt is likely to precipitate in the mixed solvent, which is not conducive to the complexation of the aluminum salt with fumarate on the glass fiber substrate to form aluminum fumarate MOF.

[0022] The glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent prepared by the above synthesis method.

[0023] The application of the above glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent in a rotary dehumidifier.

[0024] Example 1: A synthesis method of a glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent, comprising the following steps: S1. Under the condition of magnetic stirring at room temperature, according to the mass ratio of molecular sieve / sodium fumarate of 5 / 5, take 8 g of 13X, 8 g of sodium fumarate and 40 mL of deionized water and add them into a 100 mL beaker. After the raw materials are evenly dispersed, add 0.8 g of chitosan hydrochloride (CTS) and 0.56 g of guar gum powder, and continue to stir to obtain a molecular sieve / sodium fumarate dispersion. Immerse the glass fiber paper with a cut size of 3×3 cm in it, take it out after continuous stirring for 0.5 h, and dry it at 120 °C to obtain a glass fiber paper containing molecular sieve / sodium fumarate.

[0025] S2. Under the condition of magnetic stirring at room temperature, take 16 g of Al 2 (SO 4 ) 3 ·18H 2 O, 8 g of ethanol and 40 mL of deionized water are added into a 100 mL beaker, and stirred until dissolved to form a uniform mixed solution. Immerse the glass fiber paper containing molecular sieve / sodium fumarate prepared in S1 in it, crystallize it in a water bath at 60 °C for 6 h, wash it three times with deionized water after the reaction, and dry it at 120 °C to obtain a glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent.

[0026] Example 2: A synthesis method of a glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent, comprising the following steps: S1. Under the condition of magnetic stirring at room temperature, according to the mass ratio of molecular sieve / sodium fumarate of 3 / 7, take 4.8 g of 13X, 11.2 g of sodium fumarate and 40 mL of deionized water and add them into a 100 mL beaker. After the raw materials are evenly dispersed, add 0.8 g of chitosan hydrochloride (CTS) and 0.56 g of guar gum powder, and continue stirring to obtain a molecular sieve / sodium fumarate dispersion. Immerse a glass fiber paper with a cut size of 3×3 cm in it, take it out after continuously stirring for 0.5 h, and dry it at 120 °C to obtain a modified molecular sieve / sodium fumarate-containing glass fiber paper.

[0027] S2. The same as Example 1.

[0028] Example 3: A method for synthesizing a glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent, comprising the following steps: S1. Under the condition of magnetic stirring at room temperature, according to the mass ratio of molecular sieve / sodium fumarate of 7 / 3, take 11.2 g of 13X, 4.8 g of sodium fumarate and 40 mL of deionized water and add them into a 100 mL beaker. After the raw materials are evenly dispersed, add 0.8 g of chitosan hydrochloride (CTS) and 0.56 g of guar gum powder, and continue stirring to obtain a molecular sieve / sodium fumarate dispersion. Immerse a glass fiber paper with a cut size of 3×3 cm in it, take it out after continuously stirring for 0.5 h, and dry it at 120 °C to obtain a modified molecular sieve / sodium fumarate-containing glass fiber paper.

[0029] S2. The same as Example 1.

[0030] Example 4: A method for synthesizing a glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent, comprising the following steps: S1. Under the condition of magnetic stirring at room temperature, according to the mass ratio of molecular sieve / sodium fumarate of 5 / 5, take 8 g of 13X, 8 g of sodium fumarate and 40 mL of deionized water and add them into a 100 mL beaker. After the raw materials are evenly dispersed, add 0.48 g of chitosan hydrochloride (CTS) and 0.56 g of guar gum powder, and continue stirring to obtain a molecular sieve / sodium fumarate dispersion. Immerse a glass fiber paper with a cut size of 3×3 cm in it, take it out after continuously stirring for 0.5 h, and dry it at 120 °C to obtain a molecular sieve / sodium fumarate-containing glass fiber paper.

[0031] S2. The same as Example 1.

[0032] Example 5: A method for synthesizing a glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent, comprising the following steps: S1. Under the condition of magnetic stirring at room temperature, according to the mass ratio of molecular sieve / sodium fumarate of 5 / 5, take 8 g of 13X, 8 g of sodium fumarate and 40 mL of deionized water and add them into a 100 mL beaker. After the raw materials are evenly dispersed, add 1 g of chitosan hydrochloride (CTS) and 0.56 g of guar gum powder, and continue stirring to obtain a molecular sieve / sodium fumarate dispersion. Immerse a glass fiber paper with a cut size of 3×3 cm in it, take it out after continuously stirring for 0.5 h, and dry it at 120 °C to obtain a glass fiber paper containing molecular sieve / sodium fumarate.

[0033] S2. The same as Example 1.

[0034] Example 6: A method for synthesizing a glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent, comprising the following steps: S1. Under the condition of magnetic stirring at room temperature, according to the mass ratio of molecular sieve / sodium fumarate of 5 / 5, take 8 g of 13X, 8 g of sodium fumarate and 40 mL of deionized water and add them into a 100 mL beaker. After the raw materials are evenly dispersed, add 0.8 g of chitosan hydrochloride (CTS) and 0.48 g of guar gum powder, and continue stirring to obtain a molecular sieve / sodium fumarate dispersion. Immerse a glass fiber paper with a cut size of 3×3 cm in it, take it out after continuously stirring for 0.5 h, and dry it at 120 °C to obtain a glass fiber paper containing molecular sieve / sodium fumarate.

[0035] S2. The same as Example 1.

[0036] Example 7: A method for synthesizing a glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent, comprising the following steps: S1. Under magnetic stirring at room temperature, according to the mass ratio of molecular sieve / sodium fumarate of 5 / 5, take 8 g of 13X, 8 g of sodium fumarate and 40 mL of deionized water and add them into a 100 mL beaker. After the raw materials are evenly dispersed, add 0.8 g of chitosan hydrochloride (CTS) and 0.7 g of guar gum powder, and continue stirring to obtain a molecular sieve / sodium fumarate dispersion. Immerse a glass fiber paper with a cut size of 3×3 cm in it, take it out after continuously stirring for 0.5 h, and dry it at 120 °C to obtain a glass fiber paper containing molecular sieve / sodium fumarate S2. The same as Example 1.

[0037] Example 8: A method for synthesizing a glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent, comprising the following steps: S1. The same as Example 1; S2. Under the condition of magnetic stirring at room temperature, take 9 g of Al 2 (SO 4 ) 3 ·18H 28 g of ethanol and 40 mL of deionized water were added to a 100 mL beaker, and stirred until dissolved to form a homogeneous mixture. The molecular sieve / fumarate sodium glass fiber paper prepared in S1 was immersed therein, crystallized in a water bath at 60 °C for 6 h, washed three times with deionized water after the reaction, and dried at 120 °C to obtain the glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent.

[0038] Example 9: A method for synthesizing a glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent, comprising the following steps: S1. The same as in Example 1; S2. Under the condition of magnetic stirring at room temperature, 30 g of Al 2 (SO 4 ) 3 ·18H 2 O, 8 g of ethanol and 40 mL of deionized water were added to a 100 mL beaker, and stirred until dissolved to form a homogeneous mixture. The molecular sieve / fumarate sodium glass fiber paper prepared in S1 was immersed therein, crystallized in a water bath at 60 °C for 6 h, washed three times with deionized water after the reaction, and dried at 120 °C to obtain the glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent.

[0039] Example 10: A method for synthesizing a glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent, comprising the following steps: S1. The same as in Example 1; S2. Under the condition of magnetic stirring at room temperature, 16 g of Al 2 (SO 4 ) 3 ·18H 2 O, 6 g of ethanol and 40 mL of deionized water were added to a 100 mL beaker, and stirred until dissolved to form a homogeneous mixture. The molecular sieve / fumarate sodium glass fiber paper prepared in S1 was immersed therein, crystallized in a water bath at 60 °C for 6 h, washed three times with deionized water after the reaction, and dried at 120 °C to obtain the glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent.

[0040] Example 11: A method for synthesizing a glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent, comprising the following steps: S1. The same as in Example 1; S2. Under the condition of magnetic stirring at room temperature, 16 g of Al 2 (SO 4 ) 3 ·18H 216 g of ethanol and 40 mL of deionized water were added to a 100 mL beaker and stirred until dissolved to form a homogeneous mixture. The molecular sieve / fumarate sodium glass fiber paper prepared in S1 was immersed therein, crystallized in a water bath at 60 °C for 6 h, washed three times with deionized water after the reaction, and dried at 120 °C to obtain a glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent.

[0041] Example 12: A method for synthesizing a glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent includes the following steps: S1. The same as Example 1; S2. Under the condition of magnetic stirring at room temperature, 16 g of Al 2 (SO 4 ) 3 ·18H 2 O, 8 g of ethanol and 40 mL of deionized water were added to a 100 mL beaker and stirred until dissolved to form a homogeneous mixture. The molecular sieve / fumarate sodium glass fiber paper prepared in S1 was immersed therein, crystallized in a water bath at 40 °C for 8 h, washed three times with deionized water after the reaction, and dried at 120 °C to obtain a glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent.

[0042] Example 13: A method for synthesizing a glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent includes the following steps: S1. The same as Example 1; S2. Under the condition of magnetic stirring at room temperature, 16 g of Al 2 (SO 4 ) 3 ·18H 2 O, 8 g of ethanol and 40 mL of deionized water were added to a 100 mL beaker and stirred until dissolved to form a homogeneous mixture. The molecular sieve / fumarate sodium glass fiber paper prepared in S1 was immersed therein, crystallized in a water bath at 70 °C for 4 h, washed three times with deionized water after the reaction, and dried at 120 °C to obtain a glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent.

[0043] Example 14: The difference from Example 1 is that 3A is used to replace 13X.

[0044] Example 15: The difference from Example 1 is that 4A is used to replace 13X.

[0045] Example 16: The difference from Example 1 is that 5A is used to replace 13X.

[0046] Example 17: The difference from Example 1 is that carboxymethyl chitosan is used to replace chitosan hydrochloride.

[0047] Example 18: The difference from Example 1 is that sodium carboxymethyl cellulose (CMC) is used to replace chitosan hydrochloride.

[0048] Example 19: The difference from Example 1 is that aluminum chloride is used to replace aluminum sulfate.

[0049] Example 20: The difference from Example 1 is that aluminum nitrate is used to replace aluminum sulfate.

[0050] Example 21: The difference from Example 1 is that alum is used to replace aluminum sulfate.

[0051] Example 22: The difference from Example 1 is that polyethylene glycol (PEG) is used to replace guar gum powder.

[0052] Example 23: The difference from Example 1 is that polyvinyl alcohol (PVA) is used to replace guar gum powder.

[0053] Example 24: The difference from Example 1 is that polyvinylpyrrolidone (PVP) is used to replace guar gum powder.

[0054] Comparative Example 1: A method for synthesizing an adsorbent, comprising the following steps: Under magnetic stirring at room temperature, take 16 g of 13X and 40 mL of deionized water and add them to a 100 mL beaker. After the raw materials are evenly dispersed, add 0.8 g of chitosan hydrochloride (CTS) and 0.56 g of guar gum powder, and continue stirring to obtain a molecular sieve dispersion. Immerse a glass fiber paper with a cut size of 3×3 cm in the molecular sieve dispersion, take it out after continuously stirring for 0.5 h, and dry it at 120 °C to obtain a glass fiber-based 13X molecular sieve adsorbent.

[0055] Comparative Example 2: A method for synthesizing an adsorbent, comprising the following steps: S1. Under magnetic stirring at room temperature, take 16 g of sodium fumarate and 40 mL of deionized water and add them to a 100 mL beaker. After the raw materials are evenly dispersed, add 0.8 g of chitosan hydrochloride (CTS) and 0.56 g of guar gum powder, and continue stirring to obtain a modified sodium fumarate solution. Immerse a glass fiber paper with a cut size of 3×3 cm in it, take it out after continuously stirring for 0.5 h, and dry it at 120 °C to obtain a glass fiber paper containing modified sodium fumarate.

[0056] S2. Under magnetic stirring at room temperature, take 16 g of Al 2 (SO 4 ) 3 ·18H 28 g of ethanol and 40 mL of deionized water were added to a 100 mL beaker to form a homogeneous mixture. The glass fiber paper containing modified sodium fumarate prepared in S1 was immersed therein, and crystallized in a water bath at 60 °C for 6 h. After the reaction, it was washed three times with deionized water and dried at 120 °C to obtain a glass fiber-based aluminum-fumaric acid MOF adsorbent.

[0057] The water vapor adsorption isotherm curves of the samples obtained in Comparative Examples 1-2 and Examples 1-3 are shown in Figure 1 the figure. It can be seen that the adsorption curves of molecular sieves / aluminum fumaric acid MOFs with different ratios can be adjusted between 13X molecular sieve and aluminum fumaric acid MOF, indicating that changing the ratio of molecular sieve / aluminum fumaric acid MOF can adjust the water vapor adsorption curve. Moreover, the molecular sieve / aluminum fumaric acid MOF composite adsorbent has a higher water vapor adsorption capacity than aluminum fumaric acid MOF at low humidity and a higher water vapor adsorption capacity than 13X molecular sieve at high humidity. Therefore, the glass fiber-based molecular sieve / aluminum fumaric acid MOF composite adsorbent can be applied to different dehumidification environments by adjusting the ratio of molecular sieve / aluminum fumaric acid MOF.

[0058] The X-ray diffraction spectra of Comparative Examples 1-2 and Example 1 are shown in Figure 2 the figure. It can be seen from Figure 2 that the XRD peak shapes and peak positions of the glass fiber-based molecular sieve / aluminum fumaric acid MOF composite adsorbent synthesized by the in-situ method (Example 1) coincide with the diffraction peaks of the glass fiber-based 13X molecular sieve adsorbent (Comparative Example 1) and the glass fiber-based aluminum-fumaric acid MOF adsorbent (Comparative Example 2), proving that the molecular sieve / aluminum fumaric acid MOF composite adsorbent can be synthesized on the surface of glass fiber by the in-situ method.

[0059] The desorption temperatures (Tp) of Comparative Examples 1-2 and Example 1 at different heating rates are shown in Table 1.

[0060] Table 1

[0061] By comparing Table 1, it can be seen that at the same heating rate, the desorption temperature of Example 1 is lower than that of Comparative Examples 1-2.

[0062] The loadings and moisture absorption rates at 25 °C and 65% RH of the glass fiber-based molecular sieve / aluminum fumaric acid MOF composite adsorbents prepared in Examples 1-7 are shown in Table 2.

[0063] Table 2

[0064] As can be seen from Table 2, the molecular sieve / aluminum fumarate MOF composite adsorbent has a high coating mass fraction, and its loading amount ranges from 65.3% to 76.4%. Its high loading amount is beneficial for the adsorbent to adsorb moisture in the air. In addition, it can be known from Examples 1 to 3 that as the mass of the molecular sieve increases, the loading amount increases relatively, and the adsorption rate decreases slightly.

[0065] In summary, the synthesis method provided by the present invention has the following advantages: (1) The glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent obtained by the present invention has a high equilibrium adsorption capacity and a low desorption temperature.

[0066] (2) For the in-situ synthesis method provided by the present invention, the prepared molecular sieve / aluminum fumarate MOF composite adsorbent has a high loading amount, and the molecular sieve / aluminum fumarate MOF has a strong binding force with the glass fiber and is not prone to falling off, solving the problem of low mass transfer and heat transfer efficiency caused by the agglomeration of powder MOFs.

[0067] (3) The glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent prepared by the present invention has a high water vapor adsorption capacity under low humidity conditions (<30% RH), and the water vapor adsorption isotherms of the molecular sieve / aluminum fumarate MOF composites with different ratios are modulated between the limits of the molecular sieve and aluminum fumarate MOF, and can be applied to different application scenarios.

[0068] The above are only the embodiments of the present invention, and do not limit the patent scope of the present invention accordingly. Any equivalent transformation made by using the content of the specification and drawings of the present invention, or directly or indirectly applied in the related technical field, shall be equally included in the patent protection scope of the present invention.

Claims

1. A method for synthesizing a glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent, characterized in that: The following steps are involved: S1. Under stirring conditions, molecular sieve, sodium fumarate, film-forming agent and thickener are added to deionized water to prepare a uniform dispersion to obtain a molecular sieve / sodium fumarate dispersion; Under stirring conditions, adding aluminum salt to a mixed solution of ethanol and deionized water to obtain a mixed solution after the aluminum salt is completely dissolved and evenly dispersed; S2, immersing the glass fiber paper in the molecular sieve / sodium fumarate dispersion until it is completely wetted, taking out and drying to obtain the glass fiber paper containing the molecular sieve / sodium fumarate; S3, immersing the glass fiber paper containing molecular sieve / sodium fumarate in the mixed solution for crystallization reaction, and then washing and drying in sequence to obtain a glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent.

2. The synthesis method according to claim 1, characterized in that In S3, the temperature of the crystallization reaction is 30-80°C.

3. The synthesis method according to claim 1, characterized in that In S3, the crystallization reaction time is 2 to 10 hours.

4. The synthesis method according to claim 1, characterized in that In S1, the mass ratio of the molecular sieve to the sodium fumarate is 2:8 to 8:

2.

5. The synthesis method according to claim 1, characterized in that In S1, the added amount of the film-forming agent is 0.5-2% of the molecular sieve / sodium fumarate dispersion.

6. The synthesis method according to claim 1, characterized in that In S1, the amount of the thickener added is 0.5-1.5% of the molecular sieve / sodium fumarate dispersion.

7. The synthesis method according to claim 1, characterized in that In S1, the mass fraction of the aluminum salt in the mixed solution is 5-25%.

8. The synthesis method according to claim 1, characterized in that In S1, when preparing the mixed solution, the mass ratio of ethanol to deionized water is 0.1~0.5:

1.

9. A glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent prepared by the synthesis method according to any one of claims 1 to 8.

10. Use of the glass fiber-based molecular sieve / aluminum fumarate MOF composite adsorbent according to claim 9 in a rotary dehumidifier.

Citation Information

Patent Citations

  • Honeycomb ceramic-based aluminum-fumaric acid MOF adsorbent and in-situ synthetic method thereof

    CN110523380A

Cited By

  • Molecular sieve-aluminum fumaric acid metal MOF composite adsorption material for rotary wheel dehumidification and preparation method of molecular sieve-aluminum fumaric acid metal MOF composite adsorption material

    CN122098523A